Innovation in Packaging and Informative Leaflets for Handwritten Batik Products Using Natural Dyes from Ciwaringin, Cirebon Regency, Indonesia - Chamidah, Nurul; Mansur, Daduk Merdika; Jannah, Nabilah Nurul (Manunggal Halim Jaya, 2025)
Ciwaringin batik is one of the distinctive batik styles from Cirebon Regency. Its uniqueness is expressed through narrative batik designs created by boarding school students and the values embedded in its motifs, writing techniques, and natural dyes. However, the value and price of this batik have not been complemented by packaging that effectively communicates the product's special qualities. This community service program, employing a research and development (R&D) approach, aims to create innovative packaging designs and informative leaflets that highlight the uniqueness of the product. During the research phase, observational studies and documentation analysis of the packaging used by artisans were conducted, followed by identifying accessible packaging innovation designs that the batik artisan community and cooperatives could easily adopt. The development stage involved designing packaging innovations and leaflets, along with testing and implementing these innovations. The program has resulted in three marketing innovations. A standardized black packaging color was introduced to showcase the elegance and sturdiness of Ciwaringin batik. This packaging is easily accessible to artisans and can be purchased in-store and online. Incorporating Ciwaringin's regional name as a logo represents the geographical indication and is collectively owned by all artisans. Using written narrative stories to convey information, enhancing access to and dissemination of knowledge about the batik.